2015
DOI: 10.1088/0031-9155/60/16/6305
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid simplified spherical harmonics with diffusion equation for light propagation in tissues

Abstract: Aiming at the limitations of the simplified spherical harmonics approximation (SPN) and diffusion equation (DE) in describing the light propagation in tissues, a hybrid simplified spherical harmonics with diffusion equation (HSDE) based diffuse light transport model is proposed. In the HSDE model, the living body is first segmented into several major organs, and then the organs are divided into high scattering tissues and other tissues. DE and SPN are employed to describe the light propagation in these two kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 62 publications
1
27
0
Order By: Relevance
“…At the same time, the reconstructed fluorescent yield is overestimated (0.367). In the authors' previous study, 10 it was observed that the CSDE model can save time (with the value varying with the ratio of high-scattering region to the whole domain) compared with the SP 3 method, which reflects in the construction of system matrixĀ. In this simulation, the time costs of the HSDE-, SP .00 GB RAM.…”
Section: Jbo Lettersmentioning
confidence: 79%
See 2 more Smart Citations
“…At the same time, the reconstructed fluorescent yield is overestimated (0.367). In the authors' previous study, 10 it was observed that the CSDE model can save time (with the value varying with the ratio of high-scattering region to the whole domain) compared with the SP 3 method, which reflects in the construction of system matrixĀ. In this simulation, the time costs of the HSDE-, SP .00 GB RAM.…”
Section: Jbo Lettersmentioning
confidence: 79%
“…Moreover, the CSDE-based reconstruction method takes less time than the SP 3 -based method for constructing the system matrix. 10 The applicability of the CSDE-based reconstruction is also demonstrated with an in vivo liver-cancer-based experiment, which shows its great potential for the detection of in situ liver cancer. A generalized Delta-Eddington phase function deduced by Cong et al 14 can also accurately model the light propagation in tissues over a wide range of optical properties and be less time consuming than the SP N .…”
Section: Jbo Lettersmentioning
confidence: 92%
See 1 more Smart Citation
“…Therefore, using a single equation or a hybrid equation integrated by wavelength to describe the light propagation in these tissues would not the best option. In our previous studies [32], [33], a fully hybrid model that integrated SP N with DE was developed to accurately and efficiently achieve this task. Since the 3 rd order SP N has the sufficient accuracy and promising efficiency, the SP 3 equation was used to construct the adaptively hybrid 3 rd simplified spherical harmonics with diffusion (AHSD) equation.…”
Section: Methodsmentioning
confidence: 99%
“…Since the 3 rd order SP N has the sufficient accuracy and promising efficiency, the SP 3 equation was used to construct the adaptively hybrid 3 rd simplified spherical harmonics with diffusion (AHSD) equation. The AHSD equation used in this work can be summarized as follows [32], [33]:…”
Section: Methodsmentioning
confidence: 99%